Coupvolution as a mechanism of regime change in the Sahel - Fain, Egor (Terrorism and political contention, 2024)
Fain et al. analyze the phenomenon of “coupvolutions” in the Sahel such as in Mali (2020–2021) and Niger (2010, 2023). They show that in these cases we are dealing with the phenomenon of a kind of “stealing” of revolutions by armies—a situation that also took place during the Egyptian Revolution of the period of the “Arab Spring”. To describe such combinations of revolutions and military coups, like we saw in Egypt, a new term has been coined, first used in 2011. Its creator, international security expert Nathan Toronto, was one of the first to draw attention to the special role played by the military in the Egyptian Revolution. This allowed him to combine in one term a “coup” and a “revolution”, marking them with a special revolutionary situation: the first phase in it is the revolutionary mobilization of the civilian population, and the second phase is a military coup, the initiators of which partially, but not completely, satisfy protesters’ demands. It is in these contexts that the notion of “coupvolution” has been used in relation to the study of revolutions in Sub-Saharan Africa.